Thermochemical energy storage properties of a barium based reactive carbonate composite - Møller, K.T.; Williamson, Kyran; Buckley, Craig; Paskevicius, Mark (ROYAL SOC CHEMISTRY, 2020)
This study introduces a new concept of reactive carbonate composites (RCCs) for thermochemical energy storage, where a BaCO3-BaSiO3mixture offers a successful thermodynamic destabilisation of BaCO3with moderate cyclic stability ∼60%, close to the theoretical maximum when considering unreactive impurities. This research presents an alternative to molten salt based energy storage technology that operates at higher temperature (850 °C) and hence maintains a higher Carnot efficiency at a competitive price level, enabling the development of a thermal energy storage system more favourable than state-of-the-art technology. Finally, the addition of catalytic quantities of CaCO3to the RCC significantly improves the reaction kinetics (one order of magnitude) through the formation of intermediate Ba2−xCaxSiO4compounds, which are hypothesised to facilitate Ba2+and O2−mobility through induced crystal defects.